e-Tutor: A Multilingual Open Educational Resource for Faculty Development to Teach Online - Rapp, Christian; Gülbahar, Yasemin; Adnan, Muge (International Review of Research in Open and Distributed Learning, 2016)
The situation in Ukraine poses severe problems to the higher education system and to students in Eastern Ukraine. Many students and academicians had been compelled to leave their university buildings and move westwards. Hence, they are forced to substitute face-to-face teaching with distance learning, often on a large scale, but within a short span of time and with limited resources. While technical/technological infrastructure often exists, know-how about conducting online teaching and respective faculty development is often found to be lacking. Within the framework of a project funded by the Swiss National Science Foundation (SNSF), a faculty development program developed in Turkey as an Open Educational Resource (e-Tutor) was adopted in three languages (English, Ukrainian, and Russian) to support qualifying university staff in teaching online. e-Tutor comprises of 14 modules, each with various content, covering different aspects of online teaching. In the following note, we briefly present the program along with the context, target group/aims, concept, genesis, initial experiences, and further development.